Assessment of temporomandibular joint dysfunction in condylar fracture of the mandible using the Helkimo index - Suhas, S.; Ramdas, Sharad; Lingam, P. P.; Kumar, H. R. Naveen; Sasidharan, Aashish; Aadithya, R. (Indian Journal of Plastic Surgery, 2017)
Introduction: Condylar fractures of the mandible are functionally important fractures as the condyle of the mandible being a part of the temporomandibular joint (TMJ) and can lead to TMJ dysfunction if not properly treated. Materials and Methods: This was a cross-sectional study of a total of 33 treated patients with fracture of the mandibular condyle who underwent examination as per the Helkimo index. Their dysfunction was quantified and clinicoepidemiological characteristics were assessed. It was found that majority of our patients were young males involved in a two-wheeler accident. All patients underwent intermaxillary fixation as the minimum treatment and 30% underwent open reduction and internal fixation in addition. Results: There was no statistically significant association between the degree of clinical dysfunction and factors such as age, mechanism of injury, type of condyle fracture, presence of other mandible fractures, and surgical procedure. However, dislocation of the mandibular condyle was found to be a negative prognostic factor and all these patients had some degree of dysfunction. Conclusion: The overall prevalence of TMJ dysfunction according to the Helkimo index was 90%. About 61% of patients had mild dysfunction (Di1) and 30% had moderate dysfunction (Di2). None of the patients had severe dysfunction. To conclude, the Helkimo index is a simple, effective, inexpensive, reliable screening index to assess TMJ dysfunction in condylar fractures of mandible.
Keywords: Helkimo index; mandible condyle fractures; temporomandibular joint dysfunction